The Case for Investment in Nutrition in Senegal : Analysis and Perspective - 15 Years of Experience in the Development of Nutrition Policy in Senegal - Ruel-Bergeron, Julie (World Bank, Washington, DC, 2018)
Senegal is among the few countries in Sub-Saharan Africa that have succeeded in improving their population’s nutritional status in recent decades. The prevalence of key nutrition indicators, such as the proportion of children stunted, wasted, and underweight, is lower than that in most other countries in the region, and even among the poorest segments of the population. Progress against malnutrition achieved over time notwithstanding, reversals in global funding for nutrition in Senegal neglect the still-too-high prevalence of child stunting, wasting, and micronutrient deficiencies, as well as the persistent prevalence of under- and overweight and anemia among women. Nutrition in early childhood has been deemed by the global community to be a key determinant of both labor productivity and economic growth. For Senegal, which has arguably entered its nutrition transition and which is embarking on a new, multi-sectoral approach to tackle the double and triple burdens of malnutrition, there is no better time to ramp up nutrition investment. This investment case outlines future directions in nutrition for Senegal on the basis of the plan stratégique multisectoriel de la nutrition (PSMN) and synthesizes a series of eight reports prepared for the purpose of understanding the country’s progress to date, while highlighting remaining gaps in funding and implementation for nutrition. The first section presents the developmental and economic rationales for investing in nutrition, including a review of Senegal’s unique political climate, which lends itself to the development of new, unconventional policies. The second section draws from a situation analysis, a political economy study, and an institutional performance assessment to describe ongoing barriers to good nutrition in Senegal, while the third section presents solutions on how to overcome them, in alignment with the PSMN. The fourth section presents the financial requirements for these activities, which are based on a calculation of sector-specific financial needs costed during the development of the PSMN, secured funding identified in the financing analysis study, and the costs of scaling up to 90 percent coverage as calculated in the economic analysis report.